Periodontal parameters and BANA test in patients with chronic renal failure undergoing hemodialysis - Sérgio Aparecido Torres; Odila Pereira da Silva Rosa; Mitsue Fujimaki Hayacibara; Maria do Carmo Machado Guimarães; Roberto M Hayacibara; Walter Antônio Bretz (University of São Paulo, 2010)
OBJECTIVES: The aim of this study was to analyze the periodontal parameters of patients with chronic renal failure. MATERIAL AND METHODS: The periodontal status of 16 Brazilian patients aged 29 to 53 (41.7±7.2) years with chronic renal failure (CRF) and another matched group of 14 healthy controls with periodontitis was assessed clinically and microbiologically. Probing pocket depth (PPD), gingival recession (GR), dental plaque index (PLI), gingival index (GI), and dental calculus index (CI) were the clinical parameters recorded for the entire dentition (at least 19 teeth), while the anaerobic periodontopathogen colonization in four sites with the highest PPD was evaluated using the BANA test ("PerioScan"; Oral B). RESULTS: The results for the CRF group and control group, respectively were: PPD: 1.77±0.32 and 2.65±0.53; GR: 0.58±0.56 and 0.51±0.36; PLI: 1.64±0.56 and 1.24±0.67; GI: 0.64±0.42 and 0.93±0.50; CI: 1.17±0.54 and 0.87±0.52. Comparison between groups using the "t" test revealed a significantly increased PPD (p<0.001) in the control group. Comparison of the other clincial parameters by the Mann-Whitney test showed differences only for PLI, which was significantly higher (p<0.05) in the CRF group. Spearman's test applied to each group showed a positive correlation among all clinical parameters, except for GR (p<0.05). None of the groups showed any correlation between GR and GI, while a significant negative correlation between GR and PPD was observed for the CRF group. The percentage of BANA-positive sites was 35.9% for the CRF group and 35.7% for the control group. The BANA test correlated positively with PPD only in the control group and with GR only in the CRF group. CONCLUSIONS: In spite of a higher PLI and dense anaerobic microbial population even in shallow PPD, patients with CRF exhibited better periodontal conditions than periodontitis patients, which is an evidence of altered response to local irritants.